BAHASA SEBAGAI ETIKA BERMEDIA SOSIAL (KATA “ANJAY” DAN KONTROVERSINYA) - Nadzir Ahmad Firdaus; Rania Syukria Rizqi; Farid Pribadi (MEDIAKOM : Jurnal Ilmu Komunikasi, 2021)
Recently, the word "Anjay" which we often hear in circles has generated controversy. This incident started with a well-known YouTuber, Lutfi Agizal, who took issue with this word in one of the content he made, so that it finally went viral in the media. The pros and cons of society continue to emerge, giving rise to a very serious debate. According to Lutfi, the word "Anjay" is considered to have a dirty meaning. This is because the word is a play on the word "dog" which is often used to denigrate someone's dignity. The problem is whether the word reflects this meaning if it is not used with bad intentions. With a descriptive qualitative approach and the view of Public Space by Jurgen Habermas, the researcher tries to analyze this phenomenon so that a middle point can be found regarding good language in communicating on social media. This is intended so that the interaction and communication that takes place on social media can run well, and avoid conflicts due to differences in language interpretation